Literature review: the physical condition of Pencak Silat athletes in Indonesia during the covid-19 pandemic - Indana Rohmatikan Zulfa; Supriatna Supriatna; Yulingga Nanda Hanief (Journal of Science and Education (JSE), 2022)
The development of the physical condition of Pencak silat athletes is an important aspect that must be considered. A person who has a good physical condition will be better prepared for matches, but the Covid-19 pandemic has indirectly forced the adaptation of athletes to carry out exercises with limited conditions, so it will indirectly affect the level of the physical condition of the Pencak silat athletes. The purpose of this study was to determine the physical condition of athletes in Indonesia during the COVID-19 pandemic. The research method used is a literature review with the PRISMA search flow on the Google Scholar database for the period of 2015-2021. The results of the study found five articles that matched the criteria, and there were differences in the results of the five articles on the physical condition of Pencak silat athletes in various regions and the physical condition of Pencak silat athletes during the covid-19 pandemic in the category that was quite likely to be lacking. So, there was a decrease in physical condition during the COVID-19 pandemic.